DEVELOPMENT OF POWTOON-BASED AUDIO-VISUAL LEARNING MEDIA TO IMPROVE STUDENTS' CREATIVE THINKING ABILITY ON STRAIGHT-MOTION MATERIALS - Maghfirah Zulfa; Muliani Muliani; Halimatus Sakdiah; Syafrizal Idris; Fajrul Wahdi Ginting (JURNAL EDUSCIENCE, 2023)
Research on the development of Powtoon-based audio-visual learning media aims to determine the feasibility of the product and to see whether there is an increase in students' creative thinking abilities in straight-motion material and to see student responses and teacher responses. This study uses the type of Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were questionnaires and tests, and the research subjects consisted of class X MAN 3 North Aceh. The results showed that the audio-visual learning media that had been developed was declared feasible and could improve students' creative thinking skills based on assessments: 1) The media expert obtained a percentage of 80.56% according to the criteria of "Decent" and material experts obtained a percentage of 77.33% with "Decent" criteria; 2) The teacher's response to learning media obtained a percentage of 81.33% with the criteria of "very practical"; 3) The results of student responses were very good with the level of effectiveness of the media through product trials in class XI and X which obtained an average percentage of 81.21% with the criteria "Very effective". 4) The N-gain is 0.74 with high criteria. Based on the results of this study it can be concluded that the Powtoon-based audio-visual learning media on straight motion material that has been developed is suitable for use in the learning process.Keywords: Audio Visual, Creative Thinking, Learning Media Powtoon Â AbstrakPenelitian pengembangan media pembelajaran audio visual berbasis powtoon bertujuan untuk mengetahui kelayakan produk, dan untuk melihat apakah terdapat peningkatan kemampuan berpikir kreatif peserta didik pada materi gerak lurus serta melihat respon siswa, dan respon guru. Penelitian ini menggunakan jenis penelitian Research and Development dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation).Instrumen yang digunakan dalam penelitian ini berupa angket dan tes, subjek penelitian terdiri dari kelas X MAN 3 Aceh Utara. Hasil penelitian menunjukkan bahwa media pembelajaran audio visual yang telah dikembangkan dinyatakan layak serta dapat meningkatkan kemampuan berpikir kreatif peserta didik berdasarkan penilaian:1) Tingkat kelayakan media oleh ahli media diperoleh persentase sebesar 80,51% dengan kriteria â€œLayakâ€ dan ahli materi diperoleh persentase sebesar 77,33% dengan kriteria â€œLayakâ€; 2) Respon guru terhadap media pembelajaran diperoleh persentase sebesar 81,33% dengan kriteria â€œsangat praktisâ€; 3) Hasil respon peserta didik sangat baik dengan tingkat keefektifan media melalui uji coba produk pada kelas XI dan X yang diperoleh rata-rata persentase sebesar 81,21% dengan kriteria â€œSangat efektifâ€;4) N-gain diperoleh sebesar 0,74 dengan kriteria tinggi. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa media pembelajaran audio visual berbasis powtoon pada materi gerak lurus yang telah dikembangkan layak digunakan dalam proses pembelajaran.Kata Kunci : Audio Visual, Berpikir Kreatif, Media Pembelajaran Powtoon